Tablet Compression Optimization of Ivabradine Sustained-Release Tablet Using Full Factorial Design - Kim, Kang Min; Cao, Shugeng; Pyo, Jae Sung (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim This study aimed to qualitatively identify the ranges of the factors involved in the tablet compression process for ivabradine Sustained Release (SR) tablets. Materials and Methods A full factorial design of experiments study was used to identify three factors (pre- and main-compression force and paddle rotation time) involved in the compression process of ivabradine SR tablets. For robust tableting, three responses (content uniformity, friability, and dissolution) were evaluated as critical quality attributes via analysis of variance using Design Expert software. Results The main compression force significantly influenced dissolution (1 hr, p <0.0001; 3 hr, p <0.0001; and 8 hr, p=0.0002). Precompression and paddle rotation time slightly influenced friability (p=0.0510) and content uniformity (p=0.0968). These results showed that paddle rotation time (0.27-1.37 sec), pre-compression (1.5 kN), and main compression (7.7-9.2 kN) influenced the tablet compression process of the optimal ivabradine SR tablet. Conclusion In summary, robust ranges of three factors for tableting were successfully evaluated. It can be concluded that the ranges of tablet compression leading to high quality (low friability and content uniformity, and optimal dissolution) for tableting were successfully observed by the DoE approach.
Keywords: Design of experiment; Ivabradine; Quality by design; Sustained-release tablet